The Housing Conditions of Township Neighbourhoods: Assessing Housing Performance in Langa, Cape Town - Gool, Zayd (School of Architecture, Planning and Geomatics, 2024)
The shortage in the provision of housing is one of the most urgent needs facing the majority of South Africans. The provision of proper housing has shown the stark difference in equality within the postApartheid housing landscape of South Africa. Much of the Apartheid regime had led to racial segregation through the forcible displacement of people from their places of employment and residence to government created peripheral townships neighbourhoods (Dewar & Uytenbogaardt, 1977:4). This had resulted in people of colour living within neighbourhoods with poor and subpar access to resources such as education, sanitation, employment, and critical opportunities for growth such as employment. These disadvantages had led to a major decline in the housing conditions associated with these township neighbourhoods. This dissertation set out to explore the housing conditions of township neighbourhoods within South Africa through the means of establishing a conceptual analytical framework. This provides a basis in which to assess township neighbourhoods throughout the country, through a shared history, which has shaped the housing conditions of township neighbourhoods. The conceptual analytical framework is based upon the performance criteria previously established by Dewar & Uytenbogaardt (1977). This dissertation aimed to provide a basis for which further research into housing conditions could be conducted. The main research question was focused on the physical and anthropological lens of housing conditions, and a recommended direction for further research could be that of the political and financial aspects surrounding housing condition within township neighbourhoods. The conceptual analytical framework had centred around the criteria of liveability, affordability, and sustainability, which is encapsulated by housing performance within township neighbourhoods and its relationship with scale, built form, elements of neighbourhood design, and activities. The conceptual analytical framework had been used as the basis of this dissertation to highlight the intricacies of housing conditions within township neighbourhoods as well as providing insights as to the various components surrounding it such as tenure options, housing environment and services and facilities associated with these neighbourhoods. It has also provided an understanding of the importance of the historical and contemporary interlinkages associated with housing conditions to be highlighted due to its immense impact on township neighbourhood residents' way of life.